Pengembangan Instrumen Penilaian Kognitif Eksperimen Fisika Dasar I - Irwan, Anas (UIN Alauddin Makassar, 2022)
This research is a development research (research and development) where what is desired is a valid assessment instrument and is suitable for use. The research aims to (1) To analyze the results of the development of cognitive assessment instruments for the practicum of Basic Physics Experiment I on students majoring in Physics Education UIN Alauddin Makassar theoretically and empirically. The development of assessment instruments refers to the design of the development of test instruments according to Kaharuddin Arafah which consists of 7 development steps, namely: (1) Determining the measuring scale, measuring targets and construction of measuring instruments, (2) Measuring instruments for construction results, (3) Validation of contents, (4) Temporary measuring instruments, (5) Measuring targets of trial respondents, (6) Reliability, and (7) Ready-made measuring instruments. This research was tested in the department of Physics Education in the first semester of the Class of 2021/2022 UIN Alauddin Makassar. The results of the study obtained by the Basic Physics I practicum assessment instrument theoretically produced as many as 51 question items with a reliability of 0.88 in the valid category. Meanwhile, empirically produced 48 items with the reliability of 78% of the practicum cognitive assessment instruments and their assessment rubrics meeting the reliability criteria based on trials. The results of the study obtained a practicum assessment instrument product that has been declared valid and reliable and is suitable for use as a standard assessment instrument in the Department of Physics Education UIN Alauddin Makassar.